Contemporary debates in philosophy of religion - Peterson, Michael L., 1950-; VanArragon, Raymond J. (USA : Blackwell Publication, 2004)
"This first title in Blackwell's Contemporary Debates in Philosophy series presents important philosophical issues in a stimulating and engaging manner. Twelve central questions are posed, with each question addressed by a pair of opposing essays. The debates range from vigorous disagreements between theists and their critics to arguments between theists of different philosophical and theological persuasions. Both students and scholars in the philosophy of religion will readily sense the value of rigorous debate for sharply defining the issues and paving the way for further progress."--Jacket.
Is evil evidence against belief in God? -- Does divine hiddenness justify atheism? -- Does science discredit religion? -- Is God's existence the best explanation of the universe? -- Does religious experience justify religious belief? -- Is it rational for Christians to believe in the Resurrection? -- Can only one religion be true? -- Does God take risks in governing the world? -- Does God respond to petitionary prayer? -- Is eternal damnation compatible with the Christian concept of God? -- Is morality based on God's commands? -- Should a Christian be a mind-body dualist?
Includes bibliographical references and index.
Keywords: Religion -- Philosophy; Christianity -- Philosophy